The Effectiveness of WhatsApp Media in Increasing Pregnant Women's Knowledge and Attitudes About Anemia in the Pasir Putih Community Health Center Work Area in 2026 - Taufik Kurrohman; Effa Juliana; Murniani; Siswanto (Jurnal Kebidanan Manna, 2026)
Background: In orderto prevent anaemia during pregnancy, pregnant women's attitudes and awareness about the condition are crucial. Digital media, especially WhatsApp, providesa convenient,engaging,and effective substitute for health education. Pregnant women have a significant prevalence of anaemia, according to data from the Pasir Putih Community Health Centre, underscoring the need for creative teaching materials to enhance their attitudes and understanding. Objective: By 2026, this project intends to ascertain the efficacy of WhatsApp as a tool for enhancing pregnant women's attitude sand understanding onanaemia inthe Pasir Putih Community Health Center's service area. Methods: This study employs a pre-experimental design (a single-group pre-post test) along with a quantitative approach. Asumof  individuals we reincluded in this research.The data were analyzed using the Wilcoxon test and the Kolmogorov-Smirnov normality test. Results:The research in dicates that expectant mothersin the Pasir Putih Community Health Center area are engaged in 2026 had better attitudes and knowledge regarding anaemia because to WhatsApp. Pre- and post-education assessments differed significantly, according to statistical analysis, with p-values of 0.001 for knowledge and 0.003 for attitude. Conclusion: In the Pasir Putih Community Health Centre work area in 2026, theutilizationof WhatsApp as an effective educational resource to improv epregnant women' sattitudes and understanding about anaemia had a major impact. Recommendations: Increasing theutilizationof WhatsApp as a supplementary tool for health education for expectant mothers, particularly in initiatives to avoid anaemia,so that information is provided both during and after prenatal checkups.